Getting in : a guide to acceptance at the college of your choice - Levine, Joel; May, Lawrence (New York : Random House, 1972)
Advises high school students on the most likely methods of being accepted at the college of their choice.
Keywords: Universities and colleges -- United States -- Admission; Universities and colleges -- United States -- Entrance requirements